Navigator artifact reduction in three‐dimensional late gadolinium enhancement imaging of the atria. Issue 3 (22nd October 2013) - Keegan, Jennifer; Drivas, Peter; Firmin, David N.
<x xml:space="preserve">Abstract</x> Purpose Navigator‐gated three‐dimensional (3D) late gadolinium enhancement (LGE) imaging demonstrates scarring following ablation of atrial fibrillation. An artifact originating from the slice‐selective navigator‐restore pulse is frequently present in the right pulmonary veins (PVs), obscuring the walls and making quantification of enhancement difficult. We describe a simple sequence modification to greatly reduce or remove this artifact. Methods A navigator‐gated inversion‐prepared gradient echo sequence was modified so that the slice‐selective navigator‐restore pulse was delayed in time from the nonselective preparation (NAV‐restore‐delayed). Both NAV‐restore‐delayed and conventional 3D LGE acquisitions were performed in 11 patients and the results compared. Results One patient was excluded due to severe respiratory motion artifact in both NAV‐restore‐delayed and conventional acquisitions. Moderate to severe artifact was present in 9 of the remaining 10 patients using the conventional sequence and was considerably reduced when using the NAV‐restore‐delayed sequence (ostial PV to blood pool ratio, 1.7 ± 0.5 versus 1.1 ± 0.2, respectively [P < 0.0001]; qualitative artifact scores, 2.8 ± 1.1 versus 1.2 ± 0.4, respectively [P < 0.001]). While navigator signal‐to‐noise ratio was reduced with the NAV‐restore‐delayed sequence, respiratory motion compensation was unaffected. Conclusions Shifting the navigator‐restore pulse significantly reduces or eliminates navigator artifact. This simple modification improves the quality of 3D LGE imaging and potentially aids late enhancement quantification in the atria. Magn Reson Med 72:779–785, 2014. © 2013 Wiley Periodicals, Inc.